2021
DOI: 10.1016/j.jwpe.2020.101757
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus removal from wastewater by carbonated bauxite residue under aerobic and anoxic conditions

Abstract: This study aimed at evaluating the potential use of carbonated bauxite residue (CBR) as filter substrate to upgrade phosphorus (P) removal in small wastewater treatment plants such as constructed wetlands. Comparative experiments of P removal were performed in two columns continuously fed with synthetic and real wastewater to investigate the behavior of CBR under aerobic (column A) and anoxic biotic conditions (column B). The effect of various parameters, including pH, temperature, addition of organic carbon, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Then, the supernatants from each extraction were filtered (0.45 µm filters) before P, Ca, Al, and Fe analyses. This three-step extraction protocol has also been applied to raw CBR, with the aim of quantifying the P fractions in CBR before its use for wastewater treatment, and to CBR after 140 days of continuous flow P sorption experiments (Column A in Barca et al [25]), with the aim of investigating P removal mechanisms of CBR under continuous flow conditions. All the supplementary batch experiments and chemical extractions were performed in duplicate.…”
Section: Chemical Extractionsmentioning
confidence: 99%
“…Then, the supernatants from each extraction were filtered (0.45 µm filters) before P, Ca, Al, and Fe analyses. This three-step extraction protocol has also been applied to raw CBR, with the aim of quantifying the P fractions in CBR before its use for wastewater treatment, and to CBR after 140 days of continuous flow P sorption experiments (Column A in Barca et al [25]), with the aim of investigating P removal mechanisms of CBR under continuous flow conditions. All the supplementary batch experiments and chemical extractions were performed in duplicate.…”
Section: Chemical Extractionsmentioning
confidence: 99%
“…More than 2.7 billion tonnes of bauxite residue have been stockpiled so far, and every year, 150 million tonnes are being added to this inventory [12,42]. Only 3~5% of bauxite residue, at the moment, is being repurposed for cement and ceramic production [19]. This presents the immense potential for bauxite residue as a valuable source of Sc.…”
Section: Hydrometallurgical Residuementioning
confidence: 99%
“…Bauxite residue from aluminium processing can be used as an additive in cement, concrete, bricks, and geopolymer production [79]. Recent research showed that carbonate bauxite residue can be suitable as a filter to remove phosphorus from wastewater streams [19] and also as a catalyst [81]. Mine wastes have also found applications in geopolymer preparations.…”
Section: Mineral Recoverymentioning
confidence: 99%
“…8 In contrast, industrial wastes and by-products like steel slag, bauxite residue, mine drainage residuals, and red mud demonstrate superior P adsorption capacity owing to the presence of aluminum, iron, and calcium salts. [9][10][11][12][13][14] However, the efficacy and potential impacts on ecological systems of employing these adsorbents for P adsorption depend signicantly on factors such as organic matter, alkalinity, pH, coexisting ions, and raw materials. 15,16 A recent research using mine drainage residuals for internal P control has indicated that only negligible amounts of trace metals are introduced into the water column and sediments.…”
Section: Introductionmentioning
confidence: 99%